Nitrate nitrogen enhances the efficiency of photoprotection in Leymus chinensis under drought stress - Wei, Xiaowei; Han, Lin; Xu, Nan; Sun, Mingyue; Yang, Xuechen (Frontiers in Plant Science, 2024)
Global climate change exerts a significant impact on the nitrogen supply and photosynthesis ability in land-based plants. The photosynthetic capacity of dominant grassland species is important if we are to understand carbon cycling under climate change. Drought stress is one of the major factors limiting plant photosynthesis, and nitrogen (N) is an essential nutrient involved in the photosynthetic activity of leaves.The regulatory mechanisms responsible for the effects of ammonium (NH4 + ) and nitrate (NO3 -) on the drought-induced photoinhibition of photosystem II (PSII) in plants have yet to be fully elucidated. Therefore, there is a significant need to gain a better understanding of the role of electron transport in the photoinhibition of PSII. In the present study, we conducted experiments with normal watering (LD), severe drought (MD), and extreme drought (HD) treatments, along with no nitrogen (N0), ammonium (NH4), nitrate (NO3), and mixed nitrogen (NH4NO3) treatments. We analyzed pigment accumulation, reactive oxygen species (ROS) accumulation, photosynthetic enzyme activity, photosystem activity, electron transport, and O-J-I-P kinetics. Analysis showed that increased nitrate application significantly increased the leaf chlorophyll content per unit area (Chlarea) and nitrogen content per unit area (Narea) (p < 0.05). Under HD treatment, ROS levels were lower in NO3-treated plants than in N0 plants, and there was no significant difference in photosynthetic enzyme activity between plants treated with NO3 and NH4NO3. Under drought stress, the maximum photochemical efficiency of PSII (Fv/Fm), PSII electron transport rate (ETR), and effective quantum yield of PSII (φPSII) were significant higher in NO3-treated plants (p < 0.05). Importantly, the K-band and G-band were higher in NO3-treated plants. These results suggest that drought stress hindered the formation of NADPH and ATP in N0 and NH4-treated L. chinensis plants, thus damaging the donor side of the PSII oxygen-evolving complex (OEC). After applying nitrate, higher photosynthetic enzyme and antioxidant enzyme activity not only protected PSII from photodamage under drought stress but also reduced the rate of damage in PSII during the growth of L. chinensis growth under drought stress.